PENGENALAN LOGIKA MEMBUAT PROGRAM GAME PADA ANAK-ANAK DENGAN MENGGUNAKAN APLIKASI SCRATCH - Muhammad Sholeh; I Wayan Julianta Pradnyana; Izza Wildan Ridhoni (Universitas Islam Malang, 2023)
Gaming is currently a game that both children and adults are very interested in. If not anticipated as early as possible, these games can become addictive or dependent. So that children are not only good at playing games, it is necessary to have activities that introduce the process of making game applications. With this activity, children are not only proficient in running games but know the logic in making games. The mentoring activity of introducing game logic especially to children aims to introduce the concept of game logic to children. Another benefit of this activity is to introduce logic in learning basic programming skills. The method of service activities is carried out by interviewing, socialisation, training and evaluation methods. The implementation of this training consists of material exposure and practice which includes introducing the basics of Scratch and understanding the logic used to make games. The purpose of this service activity is the improvement of basic logic and programming skills in children, as well as increasing their interest in technology and game development. The children also developed social skills and collaborative skills during the workshop activities. The results of this community service activity include children being able to use the Scratch application to create simple games and understand basic programming logic. The activities carried out can improve programming skills.